Kajian Efek Samping Obat Kemoterapi Dosetaksel pada Kanker Payudara di RS Bhayangkara Kediri - Nunuk Wijayanti; Fita Rahmawati; Pramugyono Pramugyono (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Docetaxel is a chemotherapy drug for breast cancer. Chemotherapy can cause various side effects. This study aims to provide an overview of the side effects of non-hematological and hematological drugs from the use of docetaxel chemotherapy. The non-hematological side effects observed included dermatological disorders, endocrine and metabolic disturbances, and gastrointestinal-related disorders. While the observed hematological side effects included anemia, thrombocytopenia, leukopenia, and neutropenia. The study used a cross-sectional design with prospective data collection on 45 patients undergoing a docetaxel chemotherapy regimen with a dose of 100 mg/m2 at Bhayangkara Hospital, Kediri from January 2022 - March 2023. Data collection was carried out through medical records and then identification of drug side effects was carried out through pharmacist discussion with a consultant clinician in oncology. Data evaluation was carried out descriptively in the form of percentages. The most common non-hematological side effects were hair loss, which reached 80%, followed by skin hypersensitivity reactions, which reached 73.3%, and nail changes, which reached 48.9%. At the mild severity level (grade 1), skin hypersensitivity reactions were the highest at 73.3%, followed by hair loss at 64.4%. The most significant hematological side effect is anemia. Patients experienced anemia with grade 1 as much as 37.3% and 2.2% occurred in grade 2. The side effects of docetaxel that occurred in this study were overall in the mild (grade 1) and moderate (grade 2) categories. Most patients can still tolerate the symptoms of side effects that arise. Monitoring of drug side effects and prompt management of symptoms is necessary to reduce the severity and improve patient quality of life.